Summarized information from multiple plants in one monitoring system: Advantages and disadvantages on example of boilers - Bugarski Vladimir; Nikolić Perica; Kamenko Ilija (Journal on Processing and Energy in Agriculture, 2014)
Supervisory Control And Data Acquisition (SCADA) systems reached great progress by virtue of the strong development of computer and communication technologies that allow acquisition from distributed places through modern communication networks and protocols, central data processing and presentation on high resolution screens. Summarized information in one monitoring system is the solution that provides material savings. This paper analyzes advantages and disadvantages of this approach with respect to initial costs, maintenance costs and robustness and reliability. It provides real data from implemented system in boiler plant in company Victoriaoil in Šid (Serbia). Data acquisition is configured using WinCC Siemens software. This implementation allows significant savings but preserves high performance of the system.